1971
DOI: 10.1111/j.1464-410x.1971.tb04934.x
|View full text |Cite
|
Sign up to set email alerts
|

The Results and Complications of Scrotal-Flap Urethroplasty for Stricture1

Abstract: Two years ago we described a method of urethroplasty using an inverted U-shaped scrota1 flap (Blandy et al., 1968) and referred to a preliminary series of 17 cases in whom the results seemed to be promising. We now report a larger series, comprising 70 patients, of whom 51 have completed both stages of the operation, and 21 have been followed for more than 3 years. During this time we have met with certain difficulties and complications as a result of which the original technique has been slightly modified. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
2

Year Published

1974
1974
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 2 publications
1
11
2
Order By: Relevance
“…Our 97% success rate is almost as favorable as that obtained by Blandy et al [9] who reported no recurrence of stricture or incontinence among their first 51 patients who underwent scrotal flap urethroplasty. In comparison with earlier perineal or scrotal flap operations, 1-stage repair with the superficial membranous fascia tubed flap seems technically simpler.…”
Section: Operative Techniquesupporting
confidence: 72%
“…Our 97% success rate is almost as favorable as that obtained by Blandy et al [9] who reported no recurrence of stricture or incontinence among their first 51 patients who underwent scrotal flap urethroplasty. In comparison with earlier perineal or scrotal flap operations, 1-stage repair with the superficial membranous fascia tubed flap seems technically simpler.…”
Section: Operative Techniquesupporting
confidence: 72%
“…However, in patients who have experienced failed hypospadias repair or in whom the penile skin, urethral plate, and dartos fascia are not suitable for urethral reconstruction, two-stage urethroplasty is recommended [31,49]. Historically, complex lengthy urethral strictures were treated by two-stage scrotal inlay urethroplasty [50-52]. Unfortunately, the results of scrotal inlay urethroplasties were less than optimal.…”
Section: Management Of Penile Urethral Stricturementioning
confidence: 99%
“…In 1971, Blandy published an updated, retrospective PU experience using his previously described technique (6). None of the 70 reported cases, including 51 (73%, 51/70) who went on for further completion of a second stage Johansen urethroplasty had reported recurrent strictures, incontinence or impotence during a median 3 year follow up.…”
Section: Conventional Pu: Technique and Outcomesmentioning
confidence: 99%